2010
DOI: 10.1103/physreva.82.021403
|View full text |Cite
|
Sign up to set email alerts
|

Energy correlation in above-threshold nonsequential double ionization at 800 nm

Abstract: We have investigated the energy correlation of the two electrons from nonsequential double ionization of helium atoms in 800-nm laser fields at intensities below the recollision threshold by quantum calculations. The circular arcs structure of the correlated electron momentum spectra reveals a resonant double-ionization process in which the two electrons transit from doubly excited states into continuum states by simultaneously absorbing and sharing excess energy in integer units of the photon energy. The effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
3
28
1
Order By: Relevance
“…With a strong field approximation calculation, it has been demonstrated that the recollision induced excitation with subsequent tunneling ionization can result in the correlated electron momentum distribution spreading in all of the quadrants [49]. The anticorrelated behavior in the correlated electron momentum distribution has also been investigated with a fully classical ensemble model [43,50] and by solving the time-dependent Schro¨dinger equation [46].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…With a strong field approximation calculation, it has been demonstrated that the recollision induced excitation with subsequent tunneling ionization can result in the correlated electron momentum distribution spreading in all of the quadrants [49]. The anticorrelated behavior in the correlated electron momentum distribution has also been investigated with a fully classical ensemble model [43,50] and by solving the time-dependent Schro¨dinger equation [46].…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that at the low laser intensity the two-electron energy spectra exhibit an intensity-independent 5U p (U p is the ponderomotive energy) cutoff [42,43]. The mechanism for the electron achieving final energy above 2U p in NSDI has been well demonstrated [44][45][46]. Two recent experiments have shown that at the low laser intensity, the two-electron momentum along the laser polarization exhibits a surprising anticorrelated behavior [47,48], which is completely different from that at the high laser intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Such energy sharing is, however, expected for non sequential ATDI [15][16][17][18][19][20], where two electrons are coher ently released and is favored in a linearly polarized pulse.…”
mentioning
confidence: 99%
“…As compared to the tunneling regime of ionization, where the electron escapes to the continuum through the potential barrier suppressed by laser field, above-threshold ionization (ATI) in the multiphoton regime [13] produces an electron of discretized energy by vertically absorbing many photons, interestingly, the channel-resolved single-electron ATI photoelectron spec troscopy [14] allows one to probe the participation of different electronic continua in strong-field single ionization of molecules. Beyond single ionization, exchanging and sharing of the absorbed multiphoton energies by the freed electrons are expected in nonsequential above-threshold double ionization (ATDI) [15][16][17][18][19], Recently, this was observed experimentally in argon atoms [20], To date, however, the experimental demonstration of ATDI is still lacking for strong-field multiphoton ionization of molecules.ATDI of molecules in the multiphoton regime is capable of resolving the rich and complicated multielectron dynam ics of molecules into distinct channels. Among the mani fold photon-induced molecular dynamics, isomerization is one of the most fundamental and interesting processes [21].…”
mentioning
confidence: 99%
“…The correlated electron momentum spectra from NSDI possess rich information, which can provide a profound insight into the recollision dynamics in NSDI. Thus, much attention has been concentrated on the correlated electron momentum spectra in many previous works and many novel characteristics have been found [7,8,10,24,25]. By means of these novel characteristics more detailed dynamics processes under the recollision mechanism in NSDI have been revealed.…”
Section: Introductionmentioning
confidence: 95%